Ump received national and international recognition for research projects - Ernie Nurazlin, Lizam (Penerbit UMP, 2015)

(untitled)
Universiti Malaysia Pahang (UMP)'s position at the national and international levels had indeed been elevated to an upper level following its participation and successes in various research project exhibitions and competitions.